Patient-reported outcomes measure for patients with cleft palate - Xia, Wenbo; Du, Meijun; Wu, Min; Chen, Zehua; Yang, Renjie; Shi, Bing; Huang, Hanyao (Frontiers in Public Health, 2024)
Cleft palate presents multifaceted challenges impacting speech, hearing, appearance, and cognition, significantly affecting patients’ quality of life (QoL). While surgical advancements aim to restore function and improve appearance, traditional clinical measures often fail to comprehensively capture patients’ experiences. Patient-reported outcomes measure (PROMs) have emerged as crucial tools in evaluating QoL, offering insights into various aspects such as esthetic results, speech function, and social integration. This review explores PROMs relevant to cleft palate complications, including velopharyngeal insufficiency, oronasal fistulas, maxillary hypoplasia, sleep-disordered breathing, and caregiver QoL. Additionally, the review highlights the need for cleft palate-specific scales to better address the unique challenges faced by patients. By incorporating PROMs, healthcare providers can achieve more personalized, patient-centered care, improve communication, and enhance treatment outcomes. Future research should focus on developing and validating specialized PROMs to further refine patient assessments and care strategies.